2017
DOI: 10.1016/j.ygyno.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Values and worries of ovarian cancer patients

Abstract: Introduction Older women with ovarian cancer (OC) are less likely to receive guideline concordant treatment. Differences in values and worries about treatment may explain why. Methods Women with OC in 2013–2015 were surveyed about values and worries at the time of initial treatment. Existing values (11 item, e.g., maintaining quality of life) and worries (12 items, e.g., treatment side effects) scales were adapted based on OC literature. Responses were very/somewhat/a little/not at all important or worried. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…A study by Pisu and colleagues involving 170 ovarian cancer patients, showed that maintaining QoL and living as long as possible were both important. In women less than 65 years old, 96.9% felt longevity was important, and 95.9% felt that preserving QoL was important, compared with 87.5% and 90.3%, respectively, in the greater than 65‐year‐old age group . Stiggelbout and associates noted that when age was adjusted for in their statistical calculations, those in relationships and with children preferred longevity .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Pisu and colleagues involving 170 ovarian cancer patients, showed that maintaining QoL and living as long as possible were both important. In women less than 65 years old, 96.9% felt longevity was important, and 95.9% felt that preserving QoL was important, compared with 87.5% and 90.3%, respectively, in the greater than 65‐year‐old age group . Stiggelbout and associates noted that when age was adjusted for in their statistical calculations, those in relationships and with children preferred longevity .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the type of cancer, patients felt that QoL and LoL were equally important when considering treatment . In the study by Pisu and colleagues involving ovarian cancer, more than 90% stated that QoL and LoL were equally important . Another study by Jenkins and associates, involving participants with ovarian cancer showed that 57% felt LoL and QoL were equally important, 9% prioritized LoL, and 33% favored QoL .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite under-representation of elderly patients (≥65 years) in clinical trials,30 it has been reported that also for elderly women with advanced epithelial ovarian cancer, combined surgery and chemotherapy is the preferred treatment and is considered feasible 16. Nevertheless, a United States study among ovarian cancer patients demonstrated that older women reported being less worried about the consequences of cancer,31 which may perhaps influence treatment considerations in this age group. Moreover, older patients seem more focused on the quality of life rather than length of life 17 25…”
Section: Discussionmentioning
confidence: 99%